PROVISION OF CLINICAL PHARMACY SERVICES THROUGH THE TELEGRAM GROUP UNDER THE CONDITIONS OF THE FULL-SCALE WAR IN UKRAINE - Andriy Zimenkovsky; Yuliya Nastyukha; Olga Boretska; Oksana Horodnycha; Marta Zayats; Oksana Lopatynska; Tetiana Ryvak; Myroslava Sekh (Acta Medica Leopoliensia)
The research aims at studying the requirement for clinical pharmacy services offered through the activity of a Telegram group after the imposition of martial law in Ukraine.